Exercise

Solve the following equation. 3(3m2)=2(3m+3) 3(3m-2)=2(3m+3)

Answer

Hint

Solution

To solve the equation, we begin by distributing the coefficients in front of both parentheses. Then, we manipulate the expression to get mm by itself on one side. Then we begin to solve for mm.
3(3m2)=2(3m+3)3(3m-2)=2(3m+3)
Multiplicera in koefficient
9m6=6m+69m-6=6m+6
9m=6m+129m=6m+12
3m=123m=12
m=4m=4
Then the solution to the equation is m=4m=4.

{{ 'ml-template-article-upsell1' | message }}

{{ 'ml-template-article-upsell2' | message }}

{{ 'ml-template-article-upsell3' | message }}